Room Temperature‐Integrated Photodetector between 5 μm and 8 μm Wavelength. Issue 2 (8th December 2022) - Nguyen, Thi Hao Nhi; Koompai, Natnicha; Turpaud, Victor; Montesinos-Ballester, Miguel; Frigerio, Jacopo; Calcaterra, Stefano; Ballabio, Andrea; Le Roux, Xavier; Coudevylle, Jean- René; Villebasse, Cédric; Bouville, David; Alonso-Ramos, Carlos; et al.
Abstract : Mid‐infrared (mid‐IR) optics has a great importance for a large number of applications in sensing, imaging, or even telecommunication. However, high‐speed and room‐temperature‐integrated photodetector (PD) operating in a wide spectrum of the mid‐IR is a critical device that is currently missing for the development of compact and efficient spectroscopic systems exploiting synchronous detection. Herein, a waveguide‐integrated PD based on a Schottky diode embedded in a graded silicon germanium waveguide is demonstrated. Photodetection is obtained in a wide spectral range from 5 to 8 μm wavelength, with responsivity reaching up to 0.1 mA W −1 . Photodetection performed in pulsed regime with laser pulse width between 50 and 200 ns indicates an operation beyond 20 MHz. Interestingly, the achieved performances indicate that this device is already suitable for on‐chip signal monitoring, while further improvement can pave the way toward advanced compact and fully integrated spectroscopic systems operating in long‐wave infrared regions. Abstract : A waveguide‐integrated photodetector based on a Schottky diode embedded in a silicon germanium waveguide is demonstrated, operating at room temperature from 5 to 8 μm wavelength, with responsivity reaching up to 0.1 mA W −1 . This result paves the way for the development of compact and efficient spectroscopic systems on chip.